2012
DOI: 10.1002/ijc.27753
|View full text |Cite
|
Sign up to set email alerts
|

Associations of insulin‐like growth factor and insulin‐like growth factor binding protein‐3 with mortality in women with breast cancer

Abstract: Elevated circulating insulin-like growth factor-1 (IGF-1), a breast epithelial cell mitogen, is associated with breast cancer development. However, its association with breast cancer survival is not established. Circulating concentrations of IGF-1 are controlled via binding proteins, including IGF Binding Protein-3 (IGFBP-3), that may modulate the association of IGF1 with breast-cancer outcomes. We measured IGF-1 and IGFBP-3 concentrations in serum from 600 women enrolled in the Health, Eating, Activity, and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 36 publications
1
48
0
1
Order By: Relevance
“…In familial breast cancer, an association between IGF1 levels and cancer development has been reported (Rosen et al 1991, Bruning et al 1995, Pasanisi et al 2011, and IGF1 may predict higher risk of recurrence in breast cancer survivors (Al-Delaimy et al 2011). Associations of IGF1 and IGF1/IGFBP3 ratio with mortality in women with breast cancer have also been reported (Duggan et al 2012, Izzo et al 2012. However, all these data need to be confirmed in larger breast cancer survivor cohorts, considering that other reports have indicated that serum concentrations of IGF1 and IGFBP3 do not correlate with breast cancer development/risk (Trinconi et al 2011).…”
Section: Ilp Molecules and Cancer Riskmentioning
confidence: 97%
“…In familial breast cancer, an association between IGF1 levels and cancer development has been reported (Rosen et al 1991, Bruning et al 1995, Pasanisi et al 2011, and IGF1 may predict higher risk of recurrence in breast cancer survivors (Al-Delaimy et al 2011). Associations of IGF1 and IGF1/IGFBP3 ratio with mortality in women with breast cancer have also been reported (Duggan et al 2012, Izzo et al 2012. However, all these data need to be confirmed in larger breast cancer survivor cohorts, considering that other reports have indicated that serum concentrations of IGF1 and IGFBP3 do not correlate with breast cancer development/risk (Trinconi et al 2011).…”
Section: Ilp Molecules and Cancer Riskmentioning
confidence: 97%
“…Moreover, due to the activation of the AMP-activated protein kinase and inhibition of MTOR, metformin might act synergistically with chemotherapeutic agents [24], and positively influence response to adjuvant chemotherapy in diabetic breast cancer patients [25]. Metformin may also work through an indirect mechanism by improving insulin sensitivity, thereby reducing insulin levels [26], and decreasing activation of IGF-1 receptors [27]. Deactivation of IGF-1 may inhibit Cyr61, and thereby suppress breast cancer growth and invasion [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemia, insulin resistance (IR) [7,8,10], and enhanced levels of insulin-like growth factor-1 (IGF-1) [11] have all been proposed as the underlying causative mechanisms, mainly on the basis of in vitro and animal studies supporting a role for insulin, insulin receptor, and IGFs in BC initiation [12][13][14] and progression [15]. These experimental findings are strengthened by indirect observations that metformin, a biguanide oral hypoglycemic agent capable of lowering insulin levels and improving IR, also might The Oncologist 2016;21:1041-1049 www.TheOncologist.com ©AlphaMed Press 2016 be effective in reducing BC incidence [8] and may beneficially act on proliferation and apoptosis markers in early BC stages [16][17][18].…”
Section: Introductionmentioning
confidence: 99%